Ensuring Pharmaceutical Product Success through Excipient QbD Efforts - Mohammad Siddique Qadir (University of Huddersfield Press, 2022)
It is essential to understand excipients' critical material attributes. A QbD strategy that includes historical data analysis and experimental work has been used in functional excipients such as Hypromellose (HPMC) to develop this understanding. The use of multivariate analysis helped to identify excipient variability and the support it could provide to improve the final product robustness.